Determinants of corporate pay-out policy and the moderating effects of firm's growth: evidence from Pakistan - Hussain, Haroon (2018)
This study investigates the determinants of dividend payout of listed firms in Pakistan from the year 2011 to 2015. The focus of the study is the life cycle theory of dividends, agency theory and signaling theory. Corporate governance indicators, firm efficiency and cash flow volatility are the main determinants used in this study. This study also includes eight corporate governance indicators namely insider ownership, ownership concentration, institutional ownership, board independence, board size, CEO duality, audit committee independence and remuneration committee. It is found that ownership concentration, institutional ownership, CEO duality, firm efficiency and cash flow volatility are the significant determinants of dividend payout in Pakistan. It is also found that growth opportunities significantly moderate the impact of ownership concentration, institutional ownership, CEO duality, firm efficiency, cash flow volatility on the dividend payout. This research is among the pioneer studies which examine the impact of firm efficiency on dividend payout. Likewise, the study is among the first attempts to incorporate growth opportunities as moderating variable in the relationship between corporate governance indicators, firm efficiency and cash flow volatility with dividend payout. The findings of current study regarding moderating effect of growth opportunities imply that agency-based life cycle theory and signaling theories are complementary theories. The direct impact of firm efficiency on dividend payout implies that management of efficient firm pays high dividend to increase their reputation in the market. Furthermore, the interaction effect of firm efficiency and growth opportunities on dividends payout imply that negative signaling effect of dividend omission may not prevail for the efficient firms. It implies that efficient firms having growth opportunities may skip dividends because there is no reason to pay dividends as an alternative governance mechanism.